Gulir Tak Berujung: Pengaruh Doomscrolling terhadap Kesehatan Mental Gen Z Karawang - Pirli, Indriyani Dewi Agita; Dimala, Cempaka Putrie; Mustika, Haryanti (EduInovasi: Journal of Basic Educational Studies, 2025)
Doomscrolling, defined as the excessive consumption of negative information on social media, has become one of the factors that worsen mental health among Generation Z. This study aims to examine the effect of doomscrolling on the mental health of Gen Z in Karawang. A quantitative method with a causal design was applied, involving 384 respondents aged 13–28 years selected through snowball sampling. The instruments used were the Doomscrolling Scale and the Mental Health Inventory (MHI-38), both of which had been tested for validity and reliability. Data analysis was conducted using simple linear regression. The findings revealed that doomscrolling had a significant effect on mental health, with a regression coefficient of -0.748 (p < 0.001) and a contribution of 75.7%. This indicates that higher levels of doomscrolling are associated with lower levels of mental health among respondents. These results highlight the urgency of promoting digital literacy, emotional regulation, and psychological interventions to help Generation Z manage social media use more wisely and maintain psychological well-being.